Food toxicology - Helferich, William (CRC Press, 2001)
This book discusses food allergens and their diagnoses, biotechnology, estrogenic factors, and antitoxicants. It also addresses more traditional topics such as pesticide residues, food additives, plant toxins, microbial toxins, and food analysis.